Processo de sistematização de ambientes de residência em software brasileiros - Duarte, Alessandro Silveira (2015)
Brazil has a limited number of organizations with quality certification, and low unskilled workers can confirm this scenario. A well qualified team can be one of the ways to improve the quality of organizations and consequently increase their competitiveness. This work presents the process of systematizing a software residency environment, whose aim is to provide qualification for employees in software organizations. The knowledge management and software residency theories were adapted in an experimental method to validate the systematization proposed. Four experiments were conducted: three were executed with computer science master students and one within a real company. The performed experiments show evidences that it is possible to systematize a residency software environment. The contribution of this work is the validation of the process and, a as consequence, the knowledge gain and transfer among employees of a software organization.